Soluble CD163 does not predict first-time myocardial infarction in patients infected with human immunodeficiency virus: a nested case–control study - Knudsen, Andreas (BioMed Central, 2013)
BACKGROUND: Soluble CD163 (sCD163) has been associated with arterial inflammation and non-calcified plaques in human immunodeficiency virus (HIV)-infected individuals and has therefore been suggested as a predictive biomarker of myocardial infarction (MI). METHODS: We conducted a nested case–control study of 55 cases with first-time MI and 182 controls matched for age, duration of antiretroviral therapy (ART), gender, smoking, and no known cardiovascular disease. All patients had four available plasma samples, 1: Before initiation of antiretroviral therapy (ART), 2: Three months after ART, 3: One year before the case’s MI, and 4: The last sample available before the case’s MI. We used conditional logistic regression to estimate the association of sCD163 with first-time MI. RESULTS: The two groups had similar HIV-parameters and cardiovascular risk factors were equally distributed. There was no significant association between sCD163 and MI neither in samples obtained one year before (OR 1.05, CI 95% 0.85 – 1.29, p = 0.66) nor two months before (OR 1.20, CI 95% 0.98-1.47 p = 0.08). CONCLUSION: sCD163 did not prove to be a useful biomarker for prediction of first-time MI in a HIV-infected population.